Pain management for the small animal practitioner - Tranquilli, William J. (Teton NewMedia, 2000)
This CD focuses on pain terminology, physiology, perception and strategies for management; analgesic drug formulary and techniques; managing pain for specific conditions and procedures including trauma patient guidelines; controlling chronic pain